Board of directors’ independence and modified audit report: An analysis of the Malaysian environment - Ishak, Suhaimi; Md Yusof, Mohd ‘Atef (Universiti Kebangsaan Malaysia, 2015)
The aim of the paper is to examine whether board of directors’ (BODs) independence has an effect on the modified audit report of the non-banking and financial companies listed on Bursa Malaysia.Data is collected from the annual reports of a sample of 300 companies for the period of 2004 to 2009. Both descriptive and multivariate analyses were employed to address the research objectives.The results indicate that BODs’ independence is negatively related to acceptance of modified audit report.In addition, a company’s higher debts or leverage may probably increase the acceptance of modified audit report; while for companies with more business segments, the acceptance of modified audit report is less.However, the size of the BODs and return on assets or asset profitability do not influence the issuance of modified audit report by the auditor.The findings provide empirical evidence on the development and importance of BODs’ independence relating to modified audit report.